2001
DOI: 10.1615/critrevbiomedeng.v29.i2.20
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of Endothelial Cell Architecture and Vascular Permeability

Abstract: Blood vessel walls form a selective barrier to the transport of materials between blood and tissue, and the endothelium contributes significantly to this barrier function. The role of the endothelium is particularly important in thin-walled vessels, such as venules, because during tissue inflammation the endothelial junctions widen in localized areas and gaps form, thus compromising the barrier function. The mechanisms of endothelial gap formation are still under question. In this review we describe what is kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 0 publications
0
74
0
Order By: Relevance
“…These results suggest that the inhibition of transendothelial permeability and migration derives from the inhibition of p38-mediated formation of stress fibres. Interestingly, formation of stress fibres also requires phosphorylation of myosin light chain (MLC) to trigger the association of F-actin with myosin (Schnittler et al, 1990;Garcia et al, 1995;Baldwin and Thurston, 2001). In this context, we found that the activation of E-selectin Figure 3 Activation of E-selectin increases transendothelial permeability -HUVEC were cultivated at confluence on a 0.4 mm pore size gelatinized polycarbonate membranes that separate the upper and bottom part of a 6.5 mm modified Boyden chamber.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results suggest that the inhibition of transendothelial permeability and migration derives from the inhibition of p38-mediated formation of stress fibres. Interestingly, formation of stress fibres also requires phosphorylation of myosin light chain (MLC) to trigger the association of F-actin with myosin (Schnittler et al, 1990;Garcia et al, 1995;Baldwin and Thurston, 2001). In this context, we found that the activation of E-selectin Figure 3 Activation of E-selectin increases transendothelial permeability -HUVEC were cultivated at confluence on a 0.4 mm pore size gelatinized polycarbonate membranes that separate the upper and bottom part of a 6.5 mm modified Boyden chamber.…”
Section: Resultsmentioning
confidence: 99%
“…E-selectin-mediated activation of ERK regulates transendothelial permeability and migration of cancer cells by regulating the Src-dependent dissociation of the VE-cadherin/b-catenin complex Adherens junctions are major structures involved in the regulation of transendothelial permeability and migration of cancer cells and leucocytes across a monolayer of endothelial cells including HUVEC (Baldwin and Thurston, 2001;Yuan, 2002;Ionescu et al, 2003;Peng et al, 2005). As a major component of adherens junctions, VE-cadherin connects adjacent endothelial cells through its extracellular domain, whereas its intracellular domain interacts with actin cytoskeleton via a family of catenins namely b-catenin (Dejana et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The endothelial lining presents a large surface area for this exchange of materials between blood and tissues (Baldwin and Thurston, 2001). The total area of this interface in human has been estimated to be about 350 m 2 (Pries et al, 2000).…”
Section: Endothelial Cell Barriermentioning
confidence: 99%
“…Microvessel permeability also has been associated with the luminal glycocalyx (Baldwin and Thurston, 2001;Curry and Michel, 1980;Michel and Curry, 1999). van den Berg et al (2003) used hyaluronidase to target hyaluronan, a component of the glycocalyx, and demonstrated that enzyme digestion not only decreased thickness of the glycocalyx, but also increased the pericapillary space, indicative of myocardial tissue edema.…”
Section: Introductionmentioning
confidence: 99%